Influence of team emotional intelligence on the performance of construction design teams - Fatima Bello; Ahmed Doko Ibrahim; Yahaya Makarfi Ibrahim; Kulomri Jipato Adogbo; Baba Adama Kolo (Journal of Construction Project Management and Innovation)
Emotional Intelligence (EI) is an important competence in teamwork settings. Predominantly, previous EI studies on teams have focused on individual-level EI, neglecting the synergy of team members in a team. Therefore, this study aimed to assess the influence of team EI on the performance of construction design teams. A mixed method approach was used to collect data by means of a questionnaire survey and focus group interviews. The questionnaire was used to collect data on team EI and team performance, while the focus group interview was conducted to give insights on team activities based on the results from the questionnaire survey. A total of 50 projects were selected, constituting eight (8) teams through convenience and purposive sampling techniques. The 8 teams consisted of 38 individuals. Thus, the questionnaire was administered to 38 respondents, of whom 17 valid responses were received, while the focus group interview was conducted with members of one team. Means, percentages and correlational analysis were utilised in the analysis of the quantitative data, while content analysis was used to analyse the qualitative data. The results obtained for team EI and performance were used for correlational analysis, which revealed that team EI has a significant positive association with the team’s self-direction and average (overall) performance, as indicated by the correlation results (τb= .432, p=.046) and (τb= .401, p=.042) respectively. The content analysis revealed that team norms improved with participation in multiple projects. This suggests that TEI contributes significantly to the performance of the construction design teams. This study holds significant practical implications for the training of construction professionals, with the potential to foster the development of high emotional intelligence (EI). Furthermore, it extends its relevance to client organizations seeking to hire design team consultants who possess emotional intelligence. To achieve improved team performance, it is suggested that client organisations consider incorporating a team-based EI assessment alongside the evaluation of technical expertise during the hiring process.